PENGARUH KOMBINASI FRUKTOSA DAN SUKROSA DALAM PENGENCER TRIS-KUNING TELUR TERHADAP KUALITAS SEMEN CAIR BABI LANDRACE: Influence of Combination of Fructose and Sucrose in Diluent Tris-Yolk Against Quality of Liquid Landrace Boars Semen - Samuel Alexsander Singga; Wilmintje Marlene Nalley; Alvrado Bire Lawa; Thomas Mata Hine (Wahana Peternakan, 2025)
The purpose of this study was to examine the effect of the combination of fructose (F) and sucrose (S) in egg yolk Tris-diluent (T-EY) on the quality of Landrace boars semen. This study used an experimental method in a complete randomized design consisting of 5 treatments and 5 repeats so that 25 experimental units were formed. The treatment in question was T0= T-EY; T1= T-EY + F 1.0% + S 0.2%; T2= T-EY + F 1.5% + S 0.2%; T3= T-EY + F 1.0% + S 0.4%; T4= T-EY + F 1.5% + S 0.4%. Good quality semen was diluted with a test diluent, then preserved at a temperature of 18-20o C. The variables studied are motility, viability, abnormalities and survival of spermatozoa. This evaluation is done every 12 hours. The results showed that at 60 hours preservation of T2 treatment resulted in the highest and significantly different spermatozoa motility (P>0.05) with all treatments with spermatozoa motility values (43.00%), spermatozoa viability (43.10%), spermatozoa abnormalities (11.40%), and spermatozoa survival (63.20 hours)). It was concluded that the combination of 1.5% fructose and 0.2% sucrose at T2 in the egg yolk Tris-diluent resulted in the best liquid semen quality in maintaining Landrace pig semen quality during low-temperature storage.     Keywords: Fructose, sucrose, qualitys of semen boars Landrace, Tris-yolk egg